Study the Effect of Pyocyanin Extracted from Pseudomonas aeruginosa on DNA Fragmentation of Human Lymphocytes Cells - R Oleiwi, Sanaa (Iraqi Journal of Science, 2023)
Eight isolates of P. aeruginosa were obtained out of 90 water samples. The isolated colonies were identified based on their morphology and biochemical characteristics, were confirmed as P. aeruginosa by the API 20E test system.The percentages of P. aeruginosa recovery in this study were 8.8.% All isolates were able to produce greenish blue pigment (pyocyanin). Pyocyanin at all concentrations was significantly increased the percentage of fragmented DNA of peripheral blood lymphocyte cells compared to control , results showed that DNA fragmentation percentage was higher in concentration 50 μg/ml (70%,74.3%) at 24 hr,48hr respectively. In summary, results of recent study demonstrate that the pyocyanin, induces apoptosis of human peripheral blood lymphocytes .